EFFECT OF AZOTOBACTER SP AND UREA FERTILIZER (N) ON EFFICIENCY (N) UPTAKE AS WELL AS TOMATO CROP YIELD - Anatje Lihiang (Lembaga Penelitian dan Pendidikan Mandala, 2022)
One of the important commodities that are widely consumed to meet nutritional and food needs, especially vegetables, is tomato (Solanum lycopersium). The need for tomatoes is increasing both in quantity and quality. But until now the need for vegetables in quantity and quality is difficult to meet using conventional agriculture. For this reason, the application of biological fertilizers that have the potential to reduce the use of inorganic fertilizers and are able to efficiently fertilize, namely the use of Azotobackter sp. The ability of these microbes to tether nitrogen from the air largely depends on environmental conditions, especially the availability of organic matter within the rhizosphere, aeration and soil moisture . Nitrogen is a very important plant nutrient. The adequacy of the supply of nitrogen in plants is characterized by the speed of plant growth and dark green leaf color. In the research of Goeswono Soepardi (1983), stated that nitrogen tethering by Azotobacter sp is only about 25 kh ha-1 N year-1. Meanwhile, the need for nitrogen in tomato plants according to Tisdale et al (1985) is 82-120 kg ha-1 N to be able to produce about 30 tons of ha-1 fresh tomatoes . This situation shows that to meet the needs of tomato plants for nitrogen, nitrogen fertilization is still needed even though they have received additional nitrogen from Azotobacter inoculated sp, that is, by fertilizing urea as a source of N. The objectives of this study are: 1. Effect of Azotobacter sp and nitrogen fertilizers on N uptake by plants as well as tomato crop yield, 2. The dose of nitrogen fertilizer on the inoculation of Azotobacter sp that gives the highest tomato yield . Based on the results of the research obtained , there was a noticeable increase in N uptake in the administration of Asotobakter sp inoculant treatment and accompanied by the application of nitrogen fertilizers than those that were not given Asotobakter sp inoculants and nitrogen fertilizers on each treatment. The highest yield of fresh tomatoes was found in the A1N3 treatment with a fresh weight of tomato fruits of 8,969.30 g / plant with a dose of nitrogen fertilizer 90 kg